BIOASSAY-GUIDED IN VITRO ANTIBACTERIAL ACTIVITY OF FRACTION FROM Abelmoschus esculentus L. FRUIT - Christina Astutiningsih; Meri Meri; Nanik Astuti Rahman (Berita Biologi, 2026)
Aims: Research focuses separating antibacterial compounds from Abelmoschus esculentus (A. esculentus) against several  pathogenic bacteria including Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Pseudomonas aeruginosae using a bioassay-guided method. Methodology and results: A. esculentus fruit was extracted and its active compounds were separated and tested against several variants of gram negative bacteria and gram positive bacteria. The testing began with extracts, followed by fractions, and  subfractions. Extracts, fractions and subfractions of A. esculentus fruit were obtained all exhibiting antibacterial activity. The ethyl acetate fraction was the most active, yielding the largest inhibition zone diameter for both bacteria. The dominant compound in this fraction was quercetin accounting for 26% of the total. The ethyl acetate fraction was then separated into subfractions then tested for antibacterial and the composition of the compound was identified. One of the subfractions that gave the diameter of the inhibition zone after being separated identification using LC-MS revealed that the dominant compound in the subfraction was flavonoid identified as (3-hydroxy-2,3-dihydroimidazo [1,5-a] pyridin-8(5H)-one-5-β-glucopyranoside 42.46%, followed by quercetin 13.23%, Fraxidin 6.34%, scopoletin 1.51% and phenolic compounds such as  homovanillic acid 1.67% and 3-(4-hydroxy-3-methoxyphenyl)-n-[2-(4-hydroxyphenyl)ethyl]prop-2-enimidic acid 4.77%. Conclusions, significance and impact to study: A. esculentus Fruit has demonstrated significant antibacterial potential, with bioactive compound including flavonoid and phenolic derivate producing a greater inhibitory zone compared to positive control, Ciprofloxacin.